2016
DOI: 10.1177/0961203316638934
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in systemic lupus erythematosus concerning anxiety, depression and quality of life

Abstract: Several studies have demonstrated a high prevalence of depression and anxiety in patients with systemic lupus erythematosus (SLE); however, few data address gender differences regarding these manifestations. This study aimed to investigate gender differences in the prevalence of depressive and anxiety symptoms, and their effect on the quality of life (QOL) of male and female SLE patients. This study included 54 male SLE patients, 54 female SLE patients, 54 male controls and 54 female controls. Depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
3
28
0
2
Order By: Relevance
“…Depression and anxiety have been found to occur commonly in SLE, with higher predilection for female lupus patients . Psychiatric comorbidities also contribute to sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression and anxiety have been found to occur commonly in SLE, with higher predilection for female lupus patients . Psychiatric comorbidities also contribute to sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety have been found to occur commonly in SLE, with higher predilection for female lupus patients. 26 Due to differences in patient characteristics and different scales used to diagnose depression and anxiety, the results of the studies cannot be directly compared. Only 6% of patients in our study had fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies reported higher depression prevalence in individuals with SLE as compared to those without SLE [119,121,127]. A few studies estimated the prevalence of depression at 13% [115] and 60% [117] among adults with SLE. A retrospective cohort study of UK adults reported that 12.6% of individuals with gout were diagnosed with depression in the primary care settings [128].…”
Section: Prevalence Of Depression Among Individuals With and Withomentioning
confidence: 99%
“…Among the studies applying the HADS, the reported prevalence of depression ranged from 0% [135] to 55.8% [136], 4.1% [90] to 40.7% [92], and 13% [115] to 31.5% [116] among individuals with RA, OA, and SLE, respectively. Among the studies using the CES-D, the prevalence of depression ranged from 7.4% [59] to 60% [58], and 9.7% [97] to 46% [98] among individuals with RA and OA, respectively.…”
Section: Prevalence Of Depression Among Individuals With and Withomentioning
confidence: 99%
“…Misperceptions of the disease and mood disorders caused by poor quality of life in SLE patients worsen the prognosis and treatment adherence [11]. Therefore, assessment of the health status in SLE patients should include lupus disease activity, damage and HRQOL [12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%